INSTRUMEN PENILAIAN SIKAP SPIRITUAL PENDIDIKAN AGAMA BUDDHA DAN BUDI PEKERTI JENJANG SMP - Sulani, Puji (Jurnal Pencerahan, 2020)
This study aims to develop a valid and proper attitude assessment instrument, based on Competency Achievement Indicators derived from Basic Competencies in the Core Competencies of the spiritual attitudes of the 7th-grade junior high school of Buddhist education and manners. The type of Research and Development used the ADDIE model without doing the implementation stage. The subjects of this study were teachers, grade VII junior high school students, and experts. The instrument design was validated, tested one to one test, and tested in small groups, and then empirically tested using Aiken’s formula. The field test results were tested for validity using product-moment correlation and tested for reliability using Cronbach’s alpha formula. This study produced three prototype non-test instruments, namely an open observation sheet (journal), self-assessment questionnaires, and peer-to-peer assessment questionnaires. The observation sheet consisted of 99 key criteria of valid and appropriate spiritual attitudes based on the results of the Aiken index compatibility test with a V value of 0.83. The self-assessment questionnaire consisted of 101 statements, 95 positive statements, and 6 negative statements that are valid and have high reliability with a price of r11 of 0.978. The peer assessment questionnaire consisted of 93 statements, 77 positive statements, and 16 negative statements that are valid and have high reliability with an r11 price of 0.990.